Effectiveness of occupation-based intervention versus neurorehabilitation on ADL recovery in stroke patients - Hasanatul Lafifah; Hendri Kurniawan (Jurnal Edukasi Ilmiah Kesehatan, 2025)
Introduction: Stroke frequently results in long-term disability that compromises independence in activities of daily living (ADL). Conventional neurorehabilitation primarily targets motor components, whereas occupation-based intervention (OBI) emphasizes meaningful, client-centered activities that may enhance functional recovery. This study aimed to compare the effectiveness of OBI and conventional neurorehabilitation in improving ADL among stroke patients. Methods: A quasi-experimental pretest–posttest control group design was employed. Thirty-four post-stroke patients were recruited using purposive sampling and allocated to an OBI group (n = 16) or a neurorehabilitation group (n = 18). ADL performance was assessed using the Modified Barthel Index. Data were analyzed using paired and independent t-tests, with effect sizes calculated using Cohen’s d. Results: Both groups demonstrated significant improvements in ADL scores after intervention (p < 0.05). However, the OBI group showed a significantly greater improvement compared to the control group (p = 0.024). The effect size for OBI was moderate to high (d = 0.67), exceeding that of conventional neurorehabilitation (d = 0.47). Conclusion: Occupation-based intervention is more effective than conventional neurorehabilitation in enhancing ADL recovery among stroke patients. Incorporating meaningful, activity-centered approaches may optimize functional outcomes in post-stroke rehabilitation